Faecal Calprotectin in Treated and Untreated Children With Coeliac Disease and Juvenile Idiopathic Arthritis. Issue 5 (November 2016) - Biskou, Olga; Gardner-Medwin, Janet; Mackinder, Mary; Bertz, Martin; Clark, Clare; Svolos, Vaios; Russell, Richard K.; Edwards, Christine A.; McGrogan, Paraic; Gerasimidis, Konstantinos
Abstract : ABSTRACT: The present study aimed to provide evidence on whether children at risk of gastrointestinal inflammation have increased measurements of faecal calprotectin (FC). FC was measured in 232 children; 55 children (n = 11 treatment naïve) with juvenile idiopathic arthritis (JIA), 63 with coeliac disease (CD); 17 with new diagnosis before and after treatment on gluten-free diet and 114 controls. None of the treatment-naive children with JIA had raised FC. Four JIA patients on treatment had a raised FC but in all cases a repeat test was normal. In newly diagnosed patients with CD, the median (interquartile range) FC was higher 36.4 (26–61) than that in controls 25.0 (23–41) mg/kg ( P = 0.045) but this significantly decreased 25 (25–25) mg/kg ( P = 0.012) after 6 months on gluten-free diet. Random measurements of FC are not raised in children with JIA or CD. A significant elevation of FC in these groups is not explained by their diagnosis and therefore needs further investigation.